CLK2 blockade modulates alternative splicing compromising MYC‐driven breast tumors - Fernando Salvador; Roger R Gomis (EMBO Molecular Medicine)
Abstract MYC oncogene overexpression/amplification is common in multiple human cancers, in which it regulates proliferation, apoptosis and cell metabolism, among other processes, and its expression associates with poor prognosis. Targeting MYC presents an exciting therapeutic possibility, but developing appropriate drugs that impair protein function remains challenging. Searching for alternative therapeutic options for treating aggressive MYC‐driven cancers is thus of high clinical interest. Intriguingly, MYC‐driven cancers present vulnerability against spliceosome inhibition. In this issue of EMBO Molecular Medicine, Iwai et al (2018) tackle targeting the splicing regulatory Cdc2‐like kinase (CLKs) family. They report that a novel, orally administered CLK2 inhibitor (T‐025) induces exon skipping, which results in cancer cell growth reduction, especially in breast cancer (BCa) MYC‐driven tumors.